Efektivitas Penerapan Sistem Informasi Berbasis Digital terhadap Manajemen Keuangan di Lembaga Kemanusiaan (Dompet Ummat Kalimantan Barat 2020-2023) - Safitri, Pipi Novia; Firayanti, Yuni; Mahardhika, Tubagus (Lembaga Pendidikan dan Penelitian Manggala Institute, 2024)
This research aims to determine the effectiveness of implementation digital-based information systems in humanitarian institutions which is Dompet Ummat. The method used in this research is a descriptive quantitative method. In this method, this research used saturated sample method, meanwhile in hypothesis testing one sample test used to analyze the effect of information system on financial management toward effectiveness. This research used Microsoft excel as instrument to analyze to analyze the data. Based on the results of the research that has been carried out, it is known that the use of the information system is declared effective based on the results of the hypothesis test TCount > TTable (20.36 > 2.06), so that based on the hypothesis made it is known that H0 is rejected and Ha is accepted. So, it can be concluded that the application of a digital-based information system for financial management at the humanitarian institution Dompet Ummat was declared effective with results of 79,64%.